Recent Progress of Src Family Kinase Inhibitors as Anticancer Agents - Cao, Xin; You, Qi-Dong; Li, Zhi-Yu; Wang, Xiao-Jian; Lu, Xiao-Yun; Liu, Xiao-Rong; Xu, Dan; Liu, Bao (Mini Reviews in Medicinal Chemistry, 2008)
Src family of protein tyrosine kinases (SFKs) play key roles in regulating signal transduction in cellular processes. However, hyper-activated SFKs lead to uncontrolled cell proliferation and cancers. Many SFKs inhibitors were designed and synthesized as anticancer agents in the past several years and great progress has been made. Herein, some predominant examples of SFKs inhibitors recently developed are reviewed and special attentions are paid to the most important ATP binding site inhibitors.
Keywords: SH3